High-density lipoprotein from patients with coronary heart disease loses anti-thrombotic effects on endothelial cells: impact on arterial thrombus formation - Holy, Erik W.; Besler, Christian; Reiner, Martin F.; Camici, Giovanni G.; Manz, Jasmin; Beer, Jürg H.; Lüscher, Thomas F.; Landmesser, Ulf; Tanner, Felix C. (Thrombosis and Haemostasis, 2014)
Thrombus formation is determined by the balance between prothrombotic mediators and anti-thrombotic factors. High-density lipoprotein (HDL) from healthy subjects exerts anti-thrombotic properties. Whether this is also the case for HDL from patients with stable coronary heart disease (CHD) or acute coronary syndrome (ACS) is unknown. In human aortic endothelial cells in culture, HDL (50 μg/ml) from healthy subjects (HS) inhibited thrombin-induced tissue factor (TF) expression and activity, while HDL (50 μg/ml) from CHD and ACS patients did not. Similarly, only healthy HDL increased endothelial tissue factor pathway inhibitor (TFPI) expression and tissue plasminogen activator (tPA) release, while HDL from CHD and ACS patients had no effect. Healthy HDL inhibited thrombin-induced plasminogen activator inhibitor type 1 (PAI-1) expression, while HDL from ACS patients enhanced endothelial PAI-1 expression. Inhibition of nitric oxide (NO) formation with L-NAME (100 μmol/l) abolished the anti-thrombotic effects of healthy HDL on TF, TFPI, and tPA expression. The exogenous nitric oxide donor, DETANO, mimicked the effects of healthy HDL and counterbalanced the loss of anti-thrombotic effects of HDL from CHD and ACS patients in endothelial cells. In line with this observation, healthy HDL, in contrast to HDL from CHD and ACS patients, increased endothelial NO production. In the laser-injured carotid artery of the mouse, thrombus formation was delayed in animals treated with healthy HDL compared with mice treated with vehicle or HDL from patients with CHD or ACS. In conclusion, HDL from CHD and ACS patients loses the ability of healthy HDL to suppress TF and to increase TFPI and t-PA and instead enhances PAI-1 and arterial thrombus formation.
Keywords: Arterial thrombosis; endothelial cells; tissue factor / factor VII; animal models; nitric oxide